The Effect of Discovery Learning Model Using Sunflowers in Circles on Mathematics Learning Outcomes - Deska Putriani; Chika Rahayu (International Journal of Trends in Mathematics Education Research, 2018)
This study aims to describe the effect of discovery learning model using sunflowers in circles on mathematics learning outcomes of grade VIII Junior High School Number (SMPN) 1 Pagaralam. The methods used in this study is descriptive method quantitative pretest-posttest design with control group design. The population in this study is the entire class VIII students of Junior High School Number (SMPN) 1 Pagaralam that amounted to 270 students with samples at 60 students. Data collection was taken by way of documentation and test be reserved in the form of the essay. The test was analyzed by documentation photograph and statistician with compare data result class experiment and class control, with the significance level of 5%. The result found in the discovery learning approach using sunflowers give good effect the result of learning, this is average experiment class is better than with control class.